Examining the relationship between trust and culture in the consultant-client relationship - AVAKIAN, Stephanos (Institutional Knowledge at Singapore Management University, 2010)
This chapter examines the dimensions of inter-organizational and interpersonal trust as they are manifested in the consultant–client interaction, viewed within the ‘cultural spheres’ framework (Schneider and Barsoux, 2003). The chapter argues that the alignment or misalignment of culture(s) helps foster or hinder the presence of trust in the consultant–client relationship. We support our argument by demonstrating how culture becomes an important informative resource from which consultants and clients manage their expectations and risk taking. In inter-organizational contexts, trust is developed through artifacts and formal procedures that are shared by both parties. In interpersonal contexts, trust is developed through the mutual sharing of cultural values, as manifested in the interpersonal qualities of integrity and benevolence. Cultural values are not necessarily part of the parent consulting firm but can be unique to the people working in partnership on a project. Examples of behavioural cultural values include forms of communication, constructive criticism, displays of ability, benevolence and integrity and an unhesitating voicing of opinions that can lead to a realignment of attitudes, feelings, motives and objectives.